2004
DOI: 10.1111/j.1365-2966.2004.07792.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutral hydrogen absorption at the centre of NGC 2146

Abstract: We present 1.4-GHz H I absorption line observations towards the starburst in NGC 2146, made with the Very Large Array and the Multi-Element Radio-Linked Interferometer Network. The H I gas has a rotating disc/ring structure with column densities between 6 and 18 × 10 21 atom cm −2 . The H I absorption has a uniform spatial and velocity distribution, and does not reveal any anomalous material concentration or velocity in the central region of the galaxy which might indicate an encounter with another galaxy or a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(41 reference statements)
3
9
0
Order By: Relevance
“…Finally, the radial velocities derived from H i absorption-line measurements within the central ±1.5 kpc (Tarchi et al 2004) agree with our and BCD-75's Hα line data and the CO line data, shown in Fig. 10.…”
Section: The Central Region Radial Velocities (R ≤ 4 Kpc)supporting
confidence: 86%
“…Finally, the radial velocities derived from H i absorption-line measurements within the central ±1.5 kpc (Tarchi et al 2004) agree with our and BCD-75's Hα line data and the CO line data, shown in Fig. 10.…”
Section: The Central Region Radial Velocities (R ≤ 4 Kpc)supporting
confidence: 86%
“…T peak background continuum source and that only the ground state of the molecule is populated, the total column density of the absorbing HDO/H 18 2 O can then be computed from (Comito et al 2003;Tarchi et al 2004)…”
Section: Freqmentioning
confidence: 99%
“…This bright core measures several kiloparsecs in diameter, and is a strong source of radio emission (1.4 GHz flux density ≈1 Jy, see de Bruyn 1977;Condon et al 1996;Braun et al 2007) against which HI is seen in absorption (Taramopoulos et al 2001;Tarchi et al 2004). Taramopoulos et al (2001) have presented a VLA HI map including short spacings that shows a neutral gas filament extending from the main body of galactic HI to the south over half a degree (160 kpc), as well as a large amount of gas extending out of the galaxy to the north.…”
Section: Ngc 2146mentioning
confidence: 99%
“…However, the multi-transition observations of 12 CO and 13 CO presented here allow us to characterize the overall physical condition of the central molecular gas in ways that arer not possible otherwise. Kaneko et al (1989), Tarchi et al (2004), Young et al (1988b), Irwin & Seaquist (1991), García-Burillo et al (2003), Beswick et al (2002), Meixner et al (1990), Davies et al (2004); c see Moustakas et al (2006).…”
Section: Introductionmentioning
confidence: 99%